Green synthesis of Silver Nanoparticles using different fruit peels and Comparative analysis of their Antifungal activity - Panthi, Prathima; Bhattar, S. P. Sreedhar (International Journal of Scientific Research in Biological Sciences, 2019)
The present work aimed to biologically synthesize silver nanoparticles by using the peels of fruits such as Citrus sinensis (Orange) and Punica granatum (Pomegranate) as reducing agents and testing the inhibitory effects of the biologically synthesized silver nanoparticles on two common fungal pathogens of plants- Fusarium sps. and Alternaria sps. The green synthesis of silver nanoparticles was carried out using the aqueous peel extracts of the fruits and the formation of silver nanoparticles was visualized from the colour change of the solutions to dark brown. Further characterization of the nanosilver was carried out by UV/Visible spectrophotometry and the size determination of the nanoparticles was done by SEM analysis. Their antifungal activity was tested against the isolates of Fusarium sps. and Alternaria sps. by using in vitro plate assays such as agar well diffusion assay and mycelial plug method. The results showed that both the peel extracts were potent bioreductants and mediated the synthesis of silver nanoparticles in a short time. Further, the biologically synthesized silver nanoparticles could successfully inhibit the growth of both the phytopathogens tested.